Measuring The Performance Of Guyana’s Construction Industry Using A Set Of Project Performance Benchmarking Metrics - Willis, Christopher J.; Rankin, Jeff H. (Penerbit Universiti Sains Malaysia, 2011)
A study measuring the performance of Guyana’s construction industry using a set of project performance benchmarking metrics was recently completed. The underlying premise of the study was that the aggregated performance of construction projects provides a realistic assessment of the performance of the construction industry, on the basis that construction projects are the mechanism through which the construction industry creates its tangible products. The fact that an influential government agency acted as owner of the study was critical to the data collection phase. The best approach for collecting project performance data in Guyana involves the utilisation of a researcher or team of researchers mining electronic and hard copy project documents. This study analysed approximately 270 construction projects to obtain an indication of the performance of guyana’s construction industry. It was found that sea defence projects performed the worst, whereas health facility projects performed the best. The main implication of this is that sea defence projects are likely to be the least efficient and, given their critical nature, there is an argument for urgent performance improvement interventions.